5PSQ-106 Analysis of the medication incident reports at the university children's hospital. (2nd March 2018) - Sviestina, I; Mozgis, D
Abstract : Background: Currently no national reporting system is in place in the country that would collect reports on patient safety incidents (PSI). Such a system was introduced in the Children's Hospital in 2013. 'Reporting' has very negative, meaning in society in general, because of the country's political past. Purpose: To analyse trends in reporting of PSI focusing on medication incidents reports (MIRs). Material and methods: A retrospective analysis from 1 January to 31 December 2016. Patient safety team members automatically receive alerts to emails when MIRs are submitted to the hospital intranet and have access to these MIRs and patients' medical records if more detailed information is needed. MIRs contain the following information: description of what, when and where happened, was this incident a never event, the degree of harm to the patient (from no harm to death), the medical record number and suggestions on how to avoid such an event. Harm levels were analysed under the National Patient Safety Agency definition. 1 Causal mechanisms associated with near miss (NM) reports were based on the Joint Commission patient safety event taxonomy. 2 Results: Only 72 (04%) of 18 380 patients were involved in MI reports during the study period. Two main MI groups were reported – wrong dose/strength/frequency 24 (33%) and omitted/delayed medicine or dose 21 (29%) report. Antibiotics were involved in 15 (43%)/45 reports. There were 4/72 (6%) cases reported without potential for harm and 6/72 (8%) cases, all preventable, when patients were harmed. The rest, 62 (86%) reports were classified as NM. In 22/62 (36%) cases, patients were not harmed due to capture before reaching the patient and in 40 (65%) cases, patients were not harmed due to timely intervention. Failure to perform routine tasks was in 21 (34%), poor communication in 15 (24%) and incorrect or incomplete knowledge in 11 (18%) cases. Some of the performed activities: Prepared recommendations for postoperative pain management. Pocket-guide with antibiotic dosages for surgeons. Introduction of Tall Man Letters in the CPOE system. Conclusion: Our study show a similar tendency described in the Archer et. al. study that MIR reporting is still low, and little has changed in the attitudes and behaviours towards MIR. New strategies are needed to reduce specialists' non-adherence to MIRs. References and/or Acknowledgements: 1. http://www.nrls.npsa.nhs.uk/EasySiteWeb/getresource. axdAssetID=61392 2. https://academic.oup.com/intqhc/article/17/2/95/1794432/The-JCAHO-patient-safety-event-taxonomy-a 3. Archer G, et. al. J Eval Clin Pract2017Nov 17. No conflict of interest